Developing Customer Responsive Supply Chain Strategy: An Empirical Investigation of the Relationship between Market Segmentation and Supply Chain Strategy - Godsell, Janet (Cranfield University, 2008)
The concept of the ‘supply chain’, rather than a set of independent functions, has been around for more than 25 years. Despite its theoretical longevity, many organisations still struggle to make the supply chain a reality. The supply chain is an integral part of business strategy and is the means by which customer demand is fulfilled. Alignment between marketing and supply chain strategy is critical to fulfilling customer demand in a cost-effective way. This is the primary objective of customer responsive supply chain strategy (CRSC). Over the last 10 years, research into CRSC strategy has primarily been focused on two different academic perspectives: the synthesis of lean and agile thinking, and strategic alignment. The resulting frameworks are prescriptive in their nature and not sensitive to the context-specific nature of supply chain management; a field of study that is hindered by a lack of consensual definition, limited empirical evidence, and studies limited in scope to dyadic relationships. The opportunity therefore exists to carry out empirical research that reaches beyond the dyad, looking at the development of CRSC strategy − the basis for this study being the relationship between market segmentation and supply chain strategy. The research design that was developed to address this opportunity was a multiple case study design. This provides the opportunity to look for theoretical replication of the guiding principles and generative mechanisms that underpin the development of CRSC strategy. The rigour of the research design was improved by the use of a five stage (define research parameters, instrument development, data gathering, data analysis, dissemination & theory development), three phase research design (pilot case, core cases, cross-case comparison). The research was based on the study of three contrasting supply chains, from the perspective of the focal firm. The focal firms included a small UK manufacturer of toiletry and detergent products, a large leading logistics provider (LLP) managing the European supply chain operations for a global electronics manufacturer, and a large UK retailer of health and beauty products. An important aspect of the research design is its boundary spanning nature. It crosses a minimum of two organisational boundaries and includes at least three different organisations within a given supply chain. A process-orientated unit of analysis is used based on the supply chain operations reference (SCOR ® ) model to consider the conversion of demand into supply across the supply chain. The primary research instrument is semi-structured interviews with secondary documentary sources being used for data triangulation where appropriate. The research concluded that traditional methods of segmentation (e.g. by sales value) do not provide a natural link to supply chain strategy and limit customer responsiveness. The challenge for management is to identify the right bases for customer segmentation that enable it to drive supply chain strategy. The primary output of the research was a framework for developing CRSC strategy. Concepts key to developing CRSC strategy and included within the model are: contextual drivers, supply chain strategy drivers and internal mechanisms.